Low occupancy rate of the pedicle screw in the vertebral body leads to upper instrumented vertebral fracture - Oe, Shin (Sci Rep, 2020)
Upper instrumented vertebra (UIV) fracture in adult spinal deformity surgery leads serious complications, such as spinal cord injury in 0.5–0.8%. Although tip-apex distance is important for preventing screw cut-out in proximal femoral fracture surgery, this suggest that the screw occupancy rate for bone fragments is also important. The purpose of this study was to investigate how the occupancy rate of pedicle screws (ORPS) affects UIV fracture. Patients with UIV fracture 1 year after surgery were defined as the fracture group (F); others were defined as the no fracture group (NF). ORPS, cut-out of pedicle screw (PS), medications, and bone mineral density were evaluated. Significant differences (P < 0.05) between group F (n = 58) and group NF (n = 260) were observed in age (71 years old in group F and 65 years old in group NF), diabetes medication use (19% in group F and 4% in group NF), steroid drug use (10% in group F and 2% in group NF), and ORPS (70% in group F and 76% in group NF). The cut-off value of ORPS using receiver operator characteristic analysis was 73%. Multiple logistic regression analysis identified diabetes medication use (P = 0.026, odds ratio [OR] 4.0) and ORPS < 73% (P = 0.001, OR 3.6) as significant risk factors for UIV fracture. The surgeon can’t control use of diabetes medication. However, they can replace with longer PS when ORPS < 73% is detected on radiographs taken during surgery. Further studies will be needed to better elucidate it’s use.